Ефект потоку енергії в одновимірній спін-1/2 XX моделі магнетоелектрика. Метод множника Лагранжа - Baran, O.R. (Publishing house "Academperiodika", 2021)
The Lagrange multiplier method is applied to study a nonequilibrium steady state with energy flux in the one-dimensional spin-1/2 XX model of a magnetoelectric with the Katsura–Nagaosa–Balatsky mechanism at sufficiently low temperatures. With the help of the Jordan–Wigner transformation, the problem is reduced to that with the Hamiltonian for spinless noninteracting fermions and can be solved exactly. A number of phase diagrams are plotted, and the dependences of the magnetization, electric polarization, and various susceptibilities on the magnetic and electric fields, as well as on the energy flux, are calculated.